THE POSITION OF THE SULTANATE OF OMAN REGARDING THE THREE ARAB ISLANDS, ABU MUSA, THE GREATER TUNB AND THE LESSER TUNB - Prof. Dr. Ameen Abbas Natheir; Duaa Abdulla Cheyad Majli (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The Omani position emerged during the years of the first Gulf War, the Iran-Iraq war (1980-1988 AD), where the Sultanate chose to take a position of neutrality during the war, and not to side with one of the sides, unlike the positions of the other countries of the Cooperation Council for the Arab Gulf States, which chose to stand by Iraq In the war I gave him full support.